TEACHING READING BY COLLABORATIVE STRATEGIC READING: AN ACTION RESEARCH - Yon A E; Zainal Rafli; Nuruddin Nuruddin (University of Kuningan, 2022)
English language learners experienced difficulties in understanding readings in English. This research aims to improve students’ reading comprehension by implementing Collaborative Strategic Reading (CSR) at second semester students of English Department, STKIP Panca Sakti Bekasi. This research used a Classroom Action Research (CAR) was conducted in two cycles. There are qualitative and quantitative data collected in this research. The former data were gained by analyzing field note, observation sheet and interview while the latter ones were obtained from pre-test, post-test and portfolio of pre-cycle, cycle I and cycle II. The result shows that the mean score of students’ reading performance increases in four dimensions not only on literal, interpretative, applicative but also on critical understanding. The finding indicates that the students’ mean score at pre-cycle (68) increases to 77 and to 87 in the first and second cycles respectively. For interpretative understanding, the average score at pre-cycle was 61, increasing to 69 in the first cycle and to 80 in the second cycle. For applicative understanding, the average score at pre-cycle was 62, increasing to 64 in the first cycle and to 84 in the second cycle. Finally, the critical understanding also increases, from 59 at pre-cycle to 65 in the first cycle and to 85 in the second cycle. Therefore, the implementation of CAR effectively improves the students’ reading performance.